Skeletal muscle phenotype and game performance in elite women football players - Mohr, M.; Fatouros, I. G.; Jamurtas, A. Z.; Draganidis, D.; Thomassen, M.; Oerntoft, C.; Ermidis, G.; Loules, G.; Batsilas, D.; Poulios, A.; Papanikolaou, K.; Randers, M. B.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2022)
We combined game activity analyses with skeletal muscle phenotypes and comprehensive physiological testing to elucidate factors of importance for physical performance in elite women's football. GPS-data from an experimental game, sprint and endurance testing, and muscle tissue analysis of metabolic enzyme activity, protein expression and fiber type composition were completed for international top-level women players (n = 20; age; 23 ± 4 yrs, height; 166 ± 10 cm, weight; 60 ± 8 kg; VO2max; 51 ± 6 ml/min/kg). Muscle monocarboxylate transporter 4 (MCT4) protein expression explained 46% of the variance in total game distance, while the ability to maintain high-intensity running (HIR) during the final 15 min of the game correlated to myosin heavy chain 1 (MHCI) and Na+-K+ ATPase ß1, FXYD1 (phospholemman) and superoxide dismutase 2 (SOD2) protein expression (range: r = 0.51-0.71; all p < 0.05). Total HIR distance correlated with (MHCIIa) protein expression (r = 0.51; p < 0.05), while muscle Na+/H+ exchanger 1 (NHE1) protein explained 36% of the variance in game sprint distance (p < 0.05). Total game accelerations (actions >4 m/s2) correlated with platelet endothelial cell adhesion molecule (PECAM-1) protein expression (r = 0.51; p < 0.05), while concentric knee flexor strength explained 42-62% of the variance in intense decelerations (>4 m/s2). In conclusion, for elite women players` game endurance performance and resistance to end-game fatigue were affected by monocarboxylate transporter expression and myosin heavy chain profile. HIR was also correlated to ion transporter expression and muscle antioxidative capacity. Finally, the importance of functional strength and measures of muscle vascularization in relation to total game decelerations and accelerations, respectively, illustrates the complex physiological demands in elite women's football.